Effects of Dietary Methionine or Arginine Levels on the Urinary Creatinine Excretion in Broiler Chicks - Hasegawa, Etsuko (J Poult Sci, 2017)
Two experiments were conducted to evaluate the usefulness of urinary creatinine levels as a criterion for the estimation of protein and amino acid requirements in poultry. Here we studied the effects of dietary precursor levels of creatinine, methionine and arginine, on urinary creatinine excretion in experiments. Both experiments used 15 Chunky broilers chicks that were 8 days old. The chicks were assigned to three dietary groups, with five chicks each, and were fed an experimental diet for 7 days. The experimental diets mainly consisted of corn and soybean meal, and contained deficient, adequate, or excessive methionine and arginine levels in experiments 1 and 2, respectively. Excreta were collected for the last 3 days of the feeding trial, and chicks were terminated by dislocation of the neck at the end of the feeding trial to collect their livers. Creatinine concentration in the excreta and hepatic l-arginine-glycine amidinotransferase (AGAT) activities were determined. Urinary creatinine levels increased with increasing both dietary methionine and arginine levels from deficient to adequate recommended by Japanese feeding standard (P<0.05), and then remained constant in experiments 1 and 2, respectively. The hepatic AGAT activity decreased when both dietary creatinine precursors levels were increased from deficient to adequate levels (p<0.05), and then remained constant. These results suggested that creatinine excretion was changed with both increasing dietary methionine and arginine, dose-dependently.